1994
DOI: 10.1021/j100064a032
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Molecular Rydberg State Decay for n = 10-200

Abstract: Time-resolved ZEKE (zero electron kinetic energy) spectroscopy has enabled measurements of the rates of decay of molecular Rydberg states close to (within a few cm-l of) the ionization threshold. The ion yield as a function of photon energy in this region cannot be understood without knowing both the ionization potential and the principal quantum numbers, n, of the states involved. Unfortunately, these two unknowns are linked by the equation hv = IP -R / ( n -a)*; an independent method must be used to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1

Year Published

1995
1995
1997
1997

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 13 publications
7
88
1
Order By: Relevance
“…The peak of the MATI spectrum lies at nϭ135 with a FWHM of 6 cm Ϫ1 (⌬nϭ60). On the low-energy side of the MATI peak the Rydberg series is clearly seen ͑as in previous ZEKE studies 20 ͒ and is shown in more detail in the inset in Fig. 5.…”
Section: B Mati Measurementssupporting
confidence: 67%
See 4 more Smart Citations
“…The peak of the MATI spectrum lies at nϭ135 with a FWHM of 6 cm Ϫ1 (⌬nϭ60). On the low-energy side of the MATI peak the Rydberg series is clearly seen ͑as in previous ZEKE studies 20 ͒ and is shown in more detail in the inset in Fig. 5.…”
Section: B Mati Measurementssupporting
confidence: 67%
“…The highly symmetric caged amine DABCO ͑see Fig. 1͒ is an exception, 20 and states with n up to 80 are observed here.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations